Surgical treatment of glossopharyngeal nerve schwannomas: Results of two-center study (14 patients included) and literature review - Sirko, Andrii H.; Lisianyi, Oleksandr M.; Skobska Оksana Y.; Malyi, Rostislav R.; Popovych, Iryna O.; Zemskova, Oksana V. (Ukrainian Neurosurgical Journal, 2021)
Objective: This study is aimed to analyze the outcomes of surgical treatment of glossopharyngeal schwannomas based on pre- and postoperative neurological status assessment. Materials and methods: This paper is a retrospective analysis of examination and surgical treatment of 14 patients who were operated on in two large clinics from 2018 to 2021 inclusive. When analyzing the collected data, gender, age, disease symptoms, tumor size and location, surgical approach, tumor to cranial nerves (CN) ratio, jugular foramen (JF) condition, and tumor removal volume were taken into account. All tumors were divided into groups depending on tumor location relative to the JF. Particular attention was paid to assessing cranial nerves functions. Facial nerve function was assessed as per House-Brackmann Scale (HBS), hearing function as per Gardner-Robertson Scale (GRS). Results: 3 (21.4%) patients had total tumor removal: 2 patients had type A tumors and one had type B tumor. Subtotal resection took place in 7 (50%) cases. In 4 cases, a tumor was partially removed: 3 patients had type D tumors and one had type B tumor. 3 (21.4%) patients had preoperative FN deficit (HBS Grade II) and mild dysfunction. 5 (35.7%) patients had postoperative facial nerve deficit: HBS ІІ, 2; ІІІ, 1; V, 2. Preoperative sensorineural type hearing impairment on the affected side was diagnosed in 13 (92.6%) patients. Before surgery, 6 patients had non-serviceable hearing, which remained at the same level after surgery. None of the patients with grade I or II hearing before surgery had any hearing impairment postoperatively. In 2 (14.3%) cases, hearing improved from grade V to grade III after surgery. 6 (42.9%) patients developed new neurological deficit in the caudal group CN. Postoperative deficit of the caudal group CN occurred in type D tumors in 3 patients, type A tumors 2 patients, and type B tumors one patient. Conclusions: Applying a retrosigmoid approach only makes it possible to achieve total tumor removal in case of type A tumors. To remove other tumor types, it is necessary to select approaches that enable access to the jugular foramen and infratemporal fossa. Intraoperative neurophysiological monitoring is an extremely important tool in glossopharyngeal schwannoma surgery. The most common postoperative complication is a developed or increased deficit of the caudal CN group, which can lead to persistent impairments in the patients’ quality of life. Preservation of the CN VII and VIII function in most cases is a feasible task and shall be ensured as a standard for this pathology.